Progress in the Treatment of High Altitude Cerebral Edema: Targeting REDOX Homeostasis - Li Y; Li C; Luo T; Yue T; Xiao W; Yang L; Zhang Z; Han F; Long P; Hu Y (Dove Medical Press, 2023)
Yubo Li,1,2,* Chengming Li,1,2,* Tao Luo,3,* Tian Yue,4 Wenjing Xiao,5 Ling Yang,1,2 Zaiyuan Zhang,6 Fei Han,3,* Pan Long,3 Yonghe Hu6 1School of Clinical Medicine, Chengdu University of TCM, Chengdu, People's Republic of China; 2Basic Medical Laboratory, The General Hospital of Western Theater Command, Chengdu, People's Republic of China; 3Department of Ophthalmology, The General Hospital of Western Theater Command, Chengdu, People's Republic of China; 4School of Life Science and Engineering, Southwest Jiaotong University, Chengdu, People's Republic of China; 5Department of Pharmacy, The General Hospital of Western Theater Command, Chengdu, People's Republic of China; 6College of Medicine, Southwest Jiaotong University, Chengdu, People's Republic of China*These authors contributed equally to this workCorrespondence: Pan Long, Department of Ophthalmology, The General Hospital of Western Theater Command, Rongdu Avenue #270, Chengdu, People's Republic of China, Tel +86-181-9125-6132, Email longpan1005@qq.com Yonghe Hu, College of Medicine, Southwest Jiaotong University, No. 111, North First section of the Second Ring Road, Chengdu, People's Republic of China, Tel +86-138-8059-6789, Email huyonghezyy@163.comAbstract: With the increasing of altitude activities from low-altitude people, the study of high altitude cerebral edema (HACE) has been revived. HACE is a severe acute mountain sickness associated with exposure to hypobaric hypoxia at high altitude, often characterized by disturbance of consciousness and ataxia. As for the pathogenesis of HACE, previous studies suggested that it might be related to the disorder of cerebral blood flow, the destruction of blood-brain barrier and the injury of brain parenchyma cells caused by inflammatory factors. In recent years, studies have confirmed that the imbalance of REDOX homeostasis is also involved in the pathogenesis of HACE, which mainly leads to abnormal activation of microglia and destruction of tight junction of vascular endothelial cells through the excessive production of mitochondrial-related reactive oxygen species. Therefore, this review summarizes the role of REDOX homeostasis and the potential of the treatment of REDOX homeostasis in HACE, which is of great significance to expand the understanding of the pathogenesis of HACE. Moreover, it will also be helpful to further study the possible therapy of HACE related to the key link of REDOX homeostasis.Keywords: high altitude cerebral edema, hypobaric hypoxia, REDOX homeostasis, mitochondria dysfunction, microglia